LEVEL OF SATISFACTION WITH LIFE AND QUALITY OF LIFE OF PLAYERS IN E-SPORTS (Physical Culture and Sport: Scientific Perspective, 2024)
The article provides information on the expediency of using means of motor activity to improve the quality and life satisfaction of eSports players. E-sports in Ukraine is developing at a fast pace, especially in the conditions of the pandemic and martial law. Therefore, the coaches of the cyber teams should take care of both the high professional level and the health of the players and prevent possible physical and psychological problems of the athletes.The purpose of the study is to assess the quality of life and the level of life satisfaction of eSports players.To achieve the goal, the following research methods were used: theoretical analysis, systematization and generalization of data from professional scientific and methodical literature and documentary materials, information from the global Internet; sociological, psychodiagnostic research methods (SWSL Life Satisfaction Scale (E. Diner), Life Satisfaction Index (adapted by N.V. Panin), assessment methods for determining quality of life SF-36); method of comparison and comparison; methods of mathematical statistics. The article deals with the analysis of the level of satisfaction and quality of life of players in eSports and the impact of current conditions on it. 30 students aged 17–20, who are studying under the OP "Cybersport" of the National University of Physical Education and Sports of Ukraine, took part in the study. In the conditions of martial law in our country, the ostentatious psychological health has undergone changes.It has been established that eSports players have an insufficient level of physical activity, a significant number of them feel dissatisfied with life, have an average level of health and reduced indicators of mental health, which requires justification and development of health measures aimed at increasing the level of health. motor activity and quality of life.
Keywords: quality of life; health; satisfaction; physical activity; e-Sports